Effect of TiO2 and fly ash on photocatalytic NOx abatement of engineered cementitious composites. (10th March 2020) - Xu, Mingfeng; Clack, Herek; Xia, Tian; Bao, Yi; Wu, Kai; Shi, Huisheng; Li, Victor
Highlights: TiO2 in ECC is effective in NOx abatement. Increasing fly ash content is found to enhance the NOx abatement rate and efficiency. The improvement in NOx abatement rate and efficiency is related to microstructure modification. A first-order reaction model can effectively capture the NOx abatement through PC reactions. Abstract: Titanium dioxide (TiO2 ) nanoparticles have been incorporated in cementitious composites to achieve photocatalytic (PC) functions such as self-cleaning and air purifying functions. This study experimentally investigates the effect of TiO2 nanoparticles and fly ash on the nitrogen oxides (NOx ) abatement rate and efficiency of Engineered Cementitious Composites (ECC) that has retained strain-hardening properties and tensile ductility. Emphasis is placed on understanding the fundamental mechanisms through research on the microstructures and chemical environment of the composite material. A first-order chemical reaction model is applied to analyze the PC reaction rate and residual NOx concentration. Test results indicate that the PC reaction rate and efficiency increase with the TiO2 content from 0 to 5%, and the fly ash to cement ratio from 0 to 2.2. Using the low-calcium fly ash further increases the PC reaction rate and efficiency. The microstructure change originated from different fly ash contents and types are closely related to PC efficiency changes. This study advances the fundamental knowledge for engineering the cementitious composites to achieve the optimal PC functions.